Investigation of Reflecting Reading Comprehension Strategies Through Self-Directed Learning on Higher Education Students (Universitas Negeri Semarang, 2022)
This study aims to: (1) analyze students’ difficulties in CEFR B2 reading comprehension, (2) analyze strategies used by students to improve their B2 reading comprehension, and (3) to monitor the students CEFR B2 reading comprehension through self-directed learning. This study utilized a case study method which employed 6 students of the magister program of English Language Education of a university in Jakarta. The study was conducted by observing the written self-reflection weekly data report. Based on the findings, it indicates that most students have difficulties in B2 reading in terms of lack of vocabulary knowledge, finding some detailed information, finding the main idea and finding the text context. Moreover, to solve the difficulties faced, from the findings, it is also identified that the students used their own strategies. They used context clues, using keywords, more reading practice. These are considered that have been helpful in doing the B2 reading activities. The students are able to reflect on, grow, and establish their own techniques for collecting and digesting new knowledge from what they had acquired or experienced during their learning process.